Efficient Hybrid Load Balancer for Software Defined Networks using OpenFlow Accuracy Prediction - B., Ananth (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Cloud computing is a global vision for real-world IT offerings where data and resources are integrated by web-based cloud management organizations using hardware and structured, primarily web-based packages. people at a reasonable cost. Sharing resources can cause problems with access to those resources, leading to a crash. The strategy for distributing network traffic across multiple connecting node or servers is called as load balancing. It is referred that no server is overloaded. Load control builds user responsiveness by distributing shares evenly. It also makes projects and sites more accessible to customers. The reason for this archive is to understand the billing control. It has associated structures of communication organizations over the Internet. Load balancing is an important part of a distributed computer to stay away from work overload and provide equally important support. Different statistics are used to determine system complexity